Islamic Economic Solutions to Poverty and Inequality in Indonesia: Bridging Faith, Practice, Inflation, and the Balance of the Financial System - Hadiat, Hadiat; Janwari, Yadi; Hasanuddin, Muhammad; Athoillah, Mohamad Anton (Asian Journal of Islamic Studies and Da'wah, 2025)
This research explores the role of Islamic economic solutions zakat, waqf, and Islamic microfinance in addressing poverty and inequality in Indonesia, a nation with a majority Muslim population and persistent socio-economic disparities. The study investigates how these faith-based financial tools contribute to poverty alleviation and social development, particularly amidst challenges such as inflation and financial system fragmentation. Positioned within the broader discourse on Islamic economics, this research evaluates the potential and limitations of these tools, offering new insights into their integration with modern financial systems. Using a mixed-methods approach, data were collected through surveys, interviews, and secondary analysis, focusing on the effectiveness and scalability of zakat, waqf, and Islamic microfinance. The findings reveal that while zakat provides immediate relief to 70% of recipients, its long-term impact is constrained by inflation and a lack of integration with development programs. Waqf shows potential for sustainable development, especially in education and healthcare, but suffers from underutilized assets due to inefficient management. Islamic microfinance empowers 75% of beneficiaries with increased income but faces challenges of limited loan sizes and financial literacy. The study concludes that addressing inflation, improving governance, and integrating Islamic economic tools with conventional financial systems are essential for maximizing their impact. These recommendations provide a pathway for sustainable poverty alleviation and economic empowerment in Indonesia.